2020
DOI: 10.1021/acs.jafc.0c03502
|View full text |Cite
|
Sign up to set email alerts
|

Research on a Specialty Mushroom (Pleurotus tuber-regium) as a Functional Food: Chemical Composition and Biological Activities

Abstract: Pleurotus tuber-regium (PTR) is an edible specialty mushroom that has attracted growing interest recently because of its sensory attributes, high nutritional values, and important medicinal properties. PTR is rich in bioactive polysaccharides, proteins with essential amino acids, essential fatty acids, dietary fiber, minerals, and vitamins. Current studies have shown that the nutrients and bioactive ingredients of PTR contribute to their antitumor, antihypercholesterolemic, antihypertensive, antiobesity, hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 69 publications
(146 reference statements)
1
7
0
Order By: Relevance
“…It is known that the sclerotium of W. cocos is composed of polysaccharides of linear (1→3)-β-D-glucan ( Wang et al, 2004 ). Polysaccharides isolated from the sclerotium of P. tuber-regium were identified as a triple-helix conformation with a main chain of (1→3)-β- D -glucan and branching at every third glucose by a (1→6)-β- D -glucopyranosyl unit ( Lin et al, 2020 ). Previous research on sclerotium formation mostly focused on plant diseases-related small sclerotia fungi, disclosing that the sclerotium formation was closely related to adversity-induced dormancy ( Willetts and Bullock, 1992 ; Smith et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the sclerotium of W. cocos is composed of polysaccharides of linear (1→3)-β-D-glucan ( Wang et al, 2004 ). Polysaccharides isolated from the sclerotium of P. tuber-regium were identified as a triple-helix conformation with a main chain of (1→3)-β- D -glucan and branching at every third glucose by a (1→6)-β- D -glucopyranosyl unit ( Lin et al, 2020 ). Previous research on sclerotium formation mostly focused on plant diseases-related small sclerotia fungi, disclosing that the sclerotium formation was closely related to adversity-induced dormancy ( Willetts and Bullock, 1992 ; Smith et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mushroom produces a sclerotium, or underground tuber and both the sclerotium and mushroom are edible. When ripe, the cap curls upward to form a cup-like shape, similar to that of an oyster mushroom (Pleurotus ostreatus) (Lin et al, 2020). In Nigeria, sclerotium is nutritiously consumed as food, with folkloric claims that they have potent medicinal properties against asthma, high blood pressure, cancer, inflammation, hyperlipidemia, and hyperglycemia (Okolo et al, 2020;Vishwakarma et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mushrooms offer countless industrial applications, especially in the production of lignin‐degrading enzymes and other industrial biocatalysts [2] . In addition, these organisms usually contain significant amounts of polysaccharides ( β ‐glucans), dietary fibers, unsaturated fatty acids, peptides, glycoproteins, and antioxidant compounds [3] . Furthermore, they are considered important sources of minerals, such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), phosphorus (P), and vitamins, in particular, vitamin D [4] .…”
Section: Introductionmentioning
confidence: 99%
“…[2] In addition, these organisms usually contain significant amounts of polysaccharides (β-glucans), dietary fibers, unsaturated fatty acids, peptides, glycoproteins, and antioxidant compounds. [3] Furthermore, they are considered important sources of minerals, such as sodium (Na), potassium (K), calcium (Ca), magnesium (Mg), phosphorus (P), and vitamins, in particular, vitamin D. [4] Several studies have demonstrated that mushrooms exhibit a wide range of beneficial properties for humans, such as antioxidant, antibacterial, antiviral, anticancer, immunomodulatory, and anti-inflammatory activities. [5] The genus Pleurotus encompasses several gilled white rot fungi species, known as decomposers of wood and agroindustrial wastes.…”
Section: Introductionmentioning
confidence: 99%